AUDIT ENERGI SISTEM KELISTRIKAN DI INDUSTRI BENANG - Hasan, Achmad (Jurnal Energi dan Lingkungan (Enerlink), 2009)
Energy audit is one way to plan for optimizing the supply and use of energyneeded by the industry. Portrait of the use of electrical energy used in Industrysupplied from PT.PLN (Persero) with the power contract for 23000 kVA and POJPower Jatiluhur with installed capacity of 5800 kVA. Especially for electric energysupplied from POJ Power, status of electricity continues to be a contract with themanager of POJ Power Jatiluhur. Based on the results of measurement of powerquality with PQA Hioki 3197 is as described in the previous section, it can beseen that: (a) Load unbalances seen from the voltage and current, (b) Fluctuatingvoltage magnitude at phase R, S and T. Even the voltage at Mill #2 reaches 238V, (c) The power factor is quite good and it ranged from 0.90 to 0.93, (d) TotalHarmonic Distortion (THD) voltage at Mill #2 lower the tolerance limit of 5%,while at Mill #3 exceeds the limit of tolerance (5.8%), (e) Voltage unbalance onMill #2 and Mill #3 below the limit of tolerance (2.5%).Kata kunci: audit, energi, listrik, faktor daya, penghematan, filter harmonik